Influence of image‐defined risk factors on the outcome of patients with localised neuroblastoma. A report from the LNESG1 study of the European International Society of Paediatric Oncology Neuroblastoma Group. Issue 9 (8th February 2015) - Monclair, Tom; Mosseri, Véronique; Cecchetto, Giovanni; De Bernardi, Bruno; Michon, Jean; Holmes, Keith
<x xml:space="preserve">Abstract</x> Background The European multicenter study LNESG1 was designed to evaluate the safety and efficacy of surgical treatment alone in patients with localised neuroblastoma. In a retrospective, observational study we examined the impact of image‐defined risk factors (IDRF) on operative complications and survival (EFS and OS). Procedure 534 patients with localised, non‐MYCN amplified neuroblastoma were recruited between 1995 and 1999. Group 1 consisted of 291 patients without IDRF (Stage L1 in the International Neuroblastoma Risk Group (INRG) staging system), all treated with primary surgery. Group 2: 118 patients with IDRF (INRG Stage L2), also treated with primary surgery. Group 3: 125 patients in whom primary surgery was not attempted, 106 receiving neo‐adjuvant chemotherapy. Results In L1 patients (Group 1) 5‐year EFS was 92% and OS 98%. In L2 patients (Group 2 and 3) EFS was 79% and OS 89%. The differences in both EFS and OS were significant. EFS and OS in Group 2 (86% and 95%) were significantly better than 73% and 83% in Group 3. In INSS stage 1, 2 and 3, EFS were respectively 94%, 81% and 76%. Except between stage 2 and 3 the differences were significant. OS were respectively 99%, 93% and 83%, all significantly different. The 17% operative complication rate in L2 patients was significantly higher than 5% in L1 patients. Conclusions In localised neuroblastoma, IDRF at diagnosis are associated with worse survival rates and higher rates of operative complications. The impact of IDRF should become an integrated part of therapy planning. Pediatr Blood Cancer 2015;62:1536–1542. © 2015 Wiley Periodicals, Inc.